Small to medium strain dynamic properties of Lanzhou loess, China. Issue 163 (December 2022) - Song, Binghui; Tsinaris, Angelos; Anastasiadis, Anastasios; Pitilakis, Kyriazis; Chen, Wenwu
Abstract: Loess is a kind of world-recognized problematic soil and, as a consequence, it is a major hazard in geotechnical engineering. This study examines the small to medium strain dynamic properties of Lanzhou intact and recompacted loess through a set of resonant column (RC) tests. The influence of soil structure on the small-strain shear modulus G 0, the variations of G / G 0, and damping ratio DT(%) with shear strain γ were analyzed and discussed. The test results show that the structure has an important influence on the dynamic properties of dry loess at small and medium strain, whereas, with the increase of moisture, its effect weakens. It is proved that a normalized correlation between G / G 0 and γ/γ0.7 is practically identical for undisturbed and recompacted loess in Lanzhou, irrespective of soil structure, which may be useful in practical applications. Highlights: The small to medium strain dynamic properties of Lanzhou loess with metastable structure were examined. Structure effect reduces the ductility in dynamic response for Lanzhou loess. The correlations between G / G 0 and γ/γ0.70 could be normalized well for Lanzhou loess, irrespective of structure effect.